2014
DOI: 10.1002/phar.1521
|View full text |Cite
|
Sign up to set email alerts
|

Balance of Academic Responsibilities of Clinical Track Pharmacy Faculty in the United States: A Survey of Select American College of Clinical Pharmacy Practice and Research Network Members

Abstract: Most of the clinical track pharmacy faculty indicated that they have insufficient time to fulfill their nonclinical academic responsibilities. Provision of protected time may alleviate some of these time constraints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 14 publications
1
16
0
Order By: Relevance
“…Many critical care pharmacists have faculty appointments in colleges or schools of pharmacy, which may add to the risk of burnout because of the added responsibilities . Expectations of critical care pharmacy faculty extend beyond patient care and include scholarship, teaching, and professional service activities . Unlike other academic health care professionals, who may be provided protected time to dedicate to academic activities, pharmacy faculty are often expected to provide full‐time patient care and complete other activities simultaneously.…”
Section: Burnout In Critical Care and Risk Among Critical Care Pharmamentioning
confidence: 99%
See 1 more Smart Citation
“…Many critical care pharmacists have faculty appointments in colleges or schools of pharmacy, which may add to the risk of burnout because of the added responsibilities . Expectations of critical care pharmacy faculty extend beyond patient care and include scholarship, teaching, and professional service activities . Unlike other academic health care professionals, who may be provided protected time to dedicate to academic activities, pharmacy faculty are often expected to provide full‐time patient care and complete other activities simultaneously.…”
Section: Burnout In Critical Care and Risk Among Critical Care Pharmamentioning
confidence: 99%
“…The UIC COP and UI Health are in close proximity allowing and requiring the critical care pharmacy faculty to be at either UIC COP and/or UI Health at any given time during the day. The close proximity may explain why the three critical care clinical track faculty participating in the model described later allocate more of their time (68.3%) to patient care and clinical teaching compared with clinical track faculty nationally (52.7%, Table ) . Furthermore, because cross‐coverage by other clinical faculty is not routinely provided while clinical faculty attend to their academic duties in the college, clinical coverage is managed in short bursts, often at a rapid rate in unpredictable intervals throughout the day.…”
Section: Off‐service Rotation Model To Reduce Burnout Among Critical mentioning
confidence: 99%
“…Our data are congruent with a survey of clinical faculty members, in which respondents indicated that the individual most responsible for evaluating performance was the academic administrator (56%), the hospital/clinical administrator (14%), or both (22%). 10 A careful review of faculty practice-related activities can help administrators at the school and practice site guide clinical faculty members regarding initiatives to pursue or areas that may need to be scaled back. Faculty practice data can also be used to draw connections with teaching and scholarship.…”
Section: Discussionmentioning
confidence: 99%
“…Many practice faculty members spend a substantial amount of time, on average 30% of their effort, engaged in direct patient care and administering clinical programs. 10 These activities often have a significant impact on patients' lives and are valued by practice partners, the school, and the university. 11 The aim of this study was to determine what processes and metrics are most commonly employed to evaluate pharmacy practice faculty members at schools of pharmacy in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical pharmacy practice comprises a significant component of workload for both preceptors and full‐time clinical faculty members 59 . Each institution, position, and relationship will have different expectations and needs, of which the faculty member or preceptor must be cognizant.…”
Section: Part 2: Updates In Faculty Developmentmentioning
confidence: 99%